2022
DOI: 10.1016/j.isci.2022.103880
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and genetic diversity of SARS-CoV-2 lineages circulating in Africa

Abstract: There is a dearth of information on COVID-19 disease dynamics in Africa. To fill this gap, we investigated the epidemiology and genetic diversity of SARS-CoV-2 lineages circulating in the continent. We retrieved 5229 complete genomes collected in 33 African countries from the GISAID database. We investigated the circulating diversity, reconstructed the viral evolutionary divergence and history, and studied the case and death trends in the continent. Almost a fifth (144/782, 18.4%) of Pango lineages found world… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Here, we have observed that a more comprehensive subsampling strategy that includes as many traits as possible (date, location, PGRHA) yields the best result in retaining the original dataset properties, as demonstrated by the high similarities of the transmission networks between the HIV-1 subtype C full and pol, and the fullCP and polCP datasets, respectively (Figure 4). Furthermore, studies that take into account sampling bias are often limited to a single replicate of a particular subsampling method (11, 13, 42, 43). We have demonstrated that this likely does not have harmful implications to the interpretation of the results as there is little variation of the overall tree topology across subsampling replicates (Figure 3), as well as in the ancestral trait reconstruction (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have observed that a more comprehensive subsampling strategy that includes as many traits as possible (date, location, PGRHA) yields the best result in retaining the original dataset properties, as demonstrated by the high similarities of the transmission networks between the HIV-1 subtype C full and pol, and the fullCP and polCP datasets, respectively (Figure 4). Furthermore, studies that take into account sampling bias are often limited to a single replicate of a particular subsampling method (11, 13, 42, 43). We have demonstrated that this likely does not have harmful implications to the interpretation of the results as there is little variation of the overall tree topology across subsampling replicates (Figure 3), as well as in the ancestral trait reconstruction (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…The use of genomic data to identify which SARS-CoV-2 strains predominated in Nigeria's first and second waves would have aided the understanding of these findings. However, African countries, including Nigeria, have contributed few SARS-CoV-2 genomic data towards the global pool [24].…”
Section: Summary and Interpretation Of Key Findingsmentioning
confidence: 99%
“…Real-time genomic surveillance of circulating SARS-CoV-2 in different parts of the world has been critical for monitoring the evolution of the virus ( 2 , 3 ). Phylogenetic analyses of SARS-CoV-2 genomes have identified emerging variants over the course of the pandemic with shifting dominance over time ( 4 6 ). Some of these variants have been classified as variants of interest (VOIs) and variants of concern (VOCs) based on their potential for rapid spread, ability to cause severe disease, capacity to evade detection, and natural-/vaccine-related immunity, as well as their ability to evade therapeutics ( 7 ).…”
Section: Introductionmentioning
confidence: 99%